Exploring Hemophilia: Understanding the Underlying Mechanisms, Diagnostic Strategies, and Therapeutic Advances - Danisa, Michelle; Maringka, Stephanie Grace; Augusto, Efrando; Catherine, Aurelia; Christian, Melinda; Febriana, Gabriella Gita; Wong, Maria Maylyn Evangelina; Tjong, Krystle Hadassa (Indonesian Journal of Life Sciences, 2025)
Hemophilia is an inherited blood disorder resulting in impaired blood clotting upon vascular damage due to defective or deficient coagulation factors. The three types of hemophilia are hemophilia A, hemophilia B, and hemophilia C, which result from the defect or deficiency of factor VIII, factor IX, and factor XI respectively. Hemophilia affects hundreds of millions of people worldwide, with the highest incidence in Asian countries including India, Bangladesh, and Indonesia. This review encompasses the epidemiology, etiology, pathophysiology, diagnosis, and treatment for hemophilia, and the literature sources were collected from other publications, including journal articles and books.